2019
DOI: 10.1002/slct.201900305
|View full text |Cite
|
Sign up to set email alerts
|

Redox Additive Electrolyte Study of Mn–MOF Electrode for Supercapacitor Applications

Abstract: The selection of appropriate electrode materials and electrolytes in addition to optimization of their combinations is a key to improve the performance of supercapacitors. Among the new electrode materials, metal‐organic frameworks (MOFs) based electrodes are attracting attention in energy storage devices, including supercapacitors and batteries. In recent years, the redox additive electrolytes have been projected as efficient options over simple aqueous electrolytes. The present work reports the synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…[ 30 ] Realizing that this COF‐carbon composite requires substantial capacitance enhancement in charge‐storage to qualify for practical usage, we resorted to a redox electrolyte system. [ 20–28 ] Here, we adopted a distinct strategy involving the use of “redox electrolyte.” We choose KI as a redox additive, owing to its exceptionally low toxicity, environmentally benign nature, and mainly for its ability to form a spectrum of redox‐active species. Under the redox potential, KI can generate stable polyiodide ions (I n ) − with different redox pairs of iodide on the surface of the electrode, such as 3I − /I 3 − , 2I − /I 2 , 2I 3 − /3I 2 , and I 2 /2IO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 30 ] Realizing that this COF‐carbon composite requires substantial capacitance enhancement in charge‐storage to qualify for practical usage, we resorted to a redox electrolyte system. [ 20–28 ] Here, we adopted a distinct strategy involving the use of “redox electrolyte.” We choose KI as a redox additive, owing to its exceptionally low toxicity, environmentally benign nature, and mainly for its ability to form a spectrum of redox‐active species. Under the redox potential, KI can generate stable polyiodide ions (I n ) − with different redox pairs of iodide on the surface of the electrode, such as 3I − /I 3 − , 2I − /I 2 , 2I 3 − /3I 2 , and I 2 /2IO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, alternatively, a great enhancement of capacitance can be achieved by introducing redox electrolyte instead of the inert electrolyte. [ 19,20 ] The improved performance in such a system is attributed to high‐speed Faradaic reactions, which impart very high pseudo‐capacitance. A variety of redox‐active electrolytes have been employed, such as Cu 2+ (1335 F g −1 a current density of 60 A g −1 ), iodine (685 F g −1 at a scan speed of 1 mV s −1 ), bromine (572 F g −1 at 2 mA cm −2 ), hydroquinone (901 F g −1 at 2.65 mA cm −2 ), methylene blue for hybrid capacitors (279 F g −1 at 0.88 mA cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a small redox peak also appeared at slow scan rates (1‐5 mV/s) attributed to the copresence of TiO 2 particles as redox‐active species in the electrode material. The appearance of this redox peak also suggested that the selected system should have a high energy density . As such, the present TiO 2 /C‐1000 composite electrode‐based SC has combined EDLC and Faradaic types of charge storage mechanisms to result in a system with features of both high charge storage capacity and their fast deliveries when needed.…”
Section: Resultsmentioning
confidence: 88%
“…Recently, redox additive based electrolytes are used to improve the performance of supercapacitor electrode materials by enhancing faradaic redox reactions inside the electrolyte. From previous reports, the addition of 0.1M K 4 [Fe(CN) 6 ] to the usual KOH electrolyte will enhance the specific capacitance tremendously [9].…”
Section: Introductionmentioning
confidence: 89%